Melatonin, circadian rhythms and breast cancer - I. I. Eremenko; V. E. Ponomarev; I. V. Vysotskaya; S. B. Polikarpova; E. A. Bogush; V. Y. Kirsanov; M. M. Davydov (ABV-press, 2023)
Breast cancer (BC) is the leading cause of morbidity and mortality of malignant neoplasms in women worldwide. In spite of a large number of studies devoted to the etiopathogenesis  of this group of malignant tumors, many questions concerning specific mechanisms of their origin and development are still unresearched. Based on numerous studies in recent years, in addition to traditional risk factors (such as hereditary factors, hormonal disorders, environmental factors, etc.), foreign and Russian authors have identified a new risk factor for BC development - the sphere of molecular disorders affecting circadian rhythms and circadian genes, as well as metabolic and regulatory intracellular pathways regulated by them. It has been shown that the balance between oncogenes and suppressor genes and processes such as neoangiogenesis, metastasis and antitumor immune response depend on the functioning of the circadian rhythm system. One of the key metabolites in the circadian rhythm regulation system is melatonin, which physiological effects extend not only to the central nervous system, but also to peripheral tissue cells. The study of the relationship between circadian rhythm disturbances, melatonin secretion and malignant tumors is one of the important tasks of modern oncology. In the present review the following aspects of this problem are considered in detail: relationships between circadian rhythms, melatonin and BC; molecular mechanisms of melatonin antitumor action in BC; therapeutic potential of melatonin in prevention and treatment of malignant breast tumors as a direct antitumor agent, a component of accompanying treatment, and as a radiosensitizer and radioprotector for radiotherapy. The purpose of this review is to investigate the problem of the relationship between the circadian rhythm system, melatonin and molecular mechanisms of development and progression of breast malignancies, as well as the therapeutic potential of melatonin in their prevention and treatment. The review is based on the study of relevant and reliable scientific articles, reviews, meta-analyses, systematic reviews, and clinical trials published in Scopus, PubMed, Web of Science and in peer-reviewed Russian journals mainly during the last 5 years.